2010
DOI: 10.1080/00288233.2010.512625
|View full text |Cite
|
Sign up to set email alerts
|

Trinexapac-ethyl delays lodging and increases seed yield in perennial ryegrass seed crops

Abstract: The plant growth regulator trinexapac-ethyl (TE) is widely used to enhance ryegrass seed yields by reducing lodging (i.e. delaying collapse of the crop). However, lodging data are usually a single evaluation related to TE rate for a particular date of measurement. In eight field trials with varying rates of TE, weekly lodging assessments were made from full head emergence and days to 50% lodging were determined. In all trials, dynamic assessment of TE treatment showed there was a strong positive correlation (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 6 publications
3
41
0
Order By: Relevance
“…The increased HI was the result of improved seed yield and small, not statistically significant reductions in biomass (Table 2). Similar effects of TE application on HI have been observed in tall fescue and in perennial ryegrass seed crops (Rolston et al, 2010;Chastain et al, 2014a). Crop canopy modification by TE enabled efficient partitioning of dry matter to seed yield in strong creeping red fescue (Zapiola et al, 2006(Zapiola et al, , 2014; however, improved carbon partitioning to seed alone could not account for the increased seed yield resulting from lodging control in perennial ryegrass .…”
Section: Tablementioning
confidence: 58%
See 2 more Smart Citations
“…The increased HI was the result of improved seed yield and small, not statistically significant reductions in biomass (Table 2). Similar effects of TE application on HI have been observed in tall fescue and in perennial ryegrass seed crops (Rolston et al, 2010;Chastain et al, 2014a). Crop canopy modification by TE enabled efficient partitioning of dry matter to seed yield in strong creeping red fescue (Zapiola et al, 2006(Zapiola et al, , 2014; however, improved carbon partitioning to seed alone could not account for the increased seed yield resulting from lodging control in perennial ryegrass .…”
Section: Tablementioning
confidence: 58%
“…adopted for use as a lodging control agent in forage and turf grass seed production (Zapiola et al, 2006;Rolston et al, 2010). Reduction in stem length and lodging by TE resulted in increased seed yield in perennial ryegrass (Lolium perenne L.) seed crops (Borm and van den Berg, 2008;Rolston et al, 2010;Koeritz et al, 2013;Chastain et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy-lodged plants of untreated plots attained the lowest TGW at both stations (Table 3). Due to lodging, growing conditions are unfavorable for seed filling because of reduced light, which has a negative impact on photosynthesis [16][17][18]. Severe lodging interferes with the transport of nutrients and moisture from the soil and, thus, with storage in developing seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Berry and Spink (2009) [19] also reported that Caramba (metconazole) application in winter rapeseed enhanced TGW by increasing leaf area index and developing optimum size of the crop canopy, which helped to reduce lodging. Growth regulator Moddus (trinexapac) treatment attained maximum value of TGW and minimal lodging at Giessen, while at RH the same treatment plots were lodged [17][18][19][20]. This was caused by a thunderstorm at the time of maturity.…”
Section: Resultsmentioning
confidence: 99%